Education and Ebola: initiating the cascade of emergency healthcare training. Issue 3 (2nd February 2015) - Eardley, Will; Bowley, D; Hunt, P; Round, J; Tarmey, N; Williams, A
Abstract : In response to the 2014 Ebola virus outbreak in West Africa, the UK deployed a Joint Inter-Agency Task Force to Sierra Leone. As well as constructing Ebola treatment units, the force supported a rapidly upscaled mass programme of training for host nation healthcare workers in basic knowledge of Ebola and personal protective equipment. A bespoke training course was developed in collaboration with the WHO and other partners over a period of 2 weeks, taught to 119 trainers the following week, and then cascaded to over 4000 Ebola workers over the following month. This article describes curriculum design, content delivery and assessment of this unique Training The Trainers course delivered in austere circumstances. Key learning points are highlighted and supplementary material is provided to inform future deployed clinical education initiatives.